2014
DOI: 10.2478/s13537-014-0213-6
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of parallel intrusion detection on graphical processors

Abstract: Intrusion detection is enormously developing field of informatics. This paper provides a survey of actual trends in intrusion detection in academic research. It presents a review about the evolution of intrusion detection systems with usage of general purpose computing on graphics processing units (GPGPU). There are many detection techniques but only some of them bring advantages of parallel computing implementation to graphical processors (GPU). The most common technique transformed into GPU is the technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A typical example of an important, and also ubiquitous, security‐related function is DPI, whereby packet payloads are matched against a set of predefined patterns. DPI imposes a significant performance overhead because of the pattern matching mechanisms that are at the core of its operation, and thus largely unavoidable (motivating a wealth of research efforts focusing on improving their performance()). Nevertheless, DPI, in one form or another, is part of many network (hardware or software) appliances and middleboxes; some examples can be seen in the work of Bremler‐Barr et al As Bremler‐Barr et al has demonstrated, extracting the DPI functionality and providing it as a common service function to various applications (combining and matching DPI patterns from different sources) can result in significant performance gains; their benchmarks, involving a single Snort‐based IDS service function, run in Mininet over OpenFlow to emulate an SDN deployment, compared with 2 separate traditional instances of Snort, showed that the former (ie, the single DPI service function) performed 67%‐86% faster than the latter.…”
Section: Service Function Chainingmentioning
confidence: 99%
“…A typical example of an important, and also ubiquitous, security‐related function is DPI, whereby packet payloads are matched against a set of predefined patterns. DPI imposes a significant performance overhead because of the pattern matching mechanisms that are at the core of its operation, and thus largely unavoidable (motivating a wealth of research efforts focusing on improving their performance()). Nevertheless, DPI, in one form or another, is part of many network (hardware or software) appliances and middleboxes; some examples can be seen in the work of Bremler‐Barr et al As Bremler‐Barr et al has demonstrated, extracting the DPI functionality and providing it as a common service function to various applications (combining and matching DPI patterns from different sources) can result in significant performance gains; their benchmarks, involving a single Snort‐based IDS service function, run in Mininet over OpenFlow to emulate an SDN deployment, compared with 2 separate traditional instances of Snort, showed that the former (ie, the single DPI service function) performed 67%‐86% faster than the latter.…”
Section: Service Function Chainingmentioning
confidence: 99%
“…This saturation causes blockage of the connection to the server [7] which could block some valuable portals such as e-learning platforms [8,9]. Some of the methods for detecting DDoS attacks use general-purpose computing on graphics processing units [10], whereas others recommend protecting networks with a firewall [11,12]. Intrusion prevention systems and intrusion detection systems use huge databases that consist of data collected during simple attacks from one place on the network [11].…”
Section: Ddos Attack Description and Recognitionmentioning
confidence: 99%
“…It is much likely that this option will be extended to the entire operating system. MPTCP is able to increase the security level of the transmitted data by using many different links to reach the destination, in contrast to the present methodology, which is based only on network protection [17][18][19] and securing of possibility of connection into this network [20,21]. The transmitted data are treated as raw binary data, which can be divided into blocks and passed to the transmission layer.…”
Section: Multipath Tcpmentioning
confidence: 99%